SINTESIS DAN KARAKTERISASI BORNEOL DARI α-PINENA GETAH PINUS (Pinus merkusii Jungh. & de Vriese) - Gunawan Pasaribu; Totok K. Waluyo; Lisna Efiyanti (BRIN Publishing, 2021)
Pine resin is obtained from a process of tapping the pine tree (Pinus merkusii Jungh. & de Vriese). After processing, pineresin will produce gondorukem and turpentine. Currently, the utilization of turpentine is mainly for cosmetic, paint, a mixture ofsolvents, antiseptics, and pharmaceuticals. Due to an increase in the added value of the turpentine product, turpentine wassynthesized into borneol. This study aimed to analyze the characteristics of borneol produced from the synthesis of α-pinene usingNaOH and KOH bases. The method was carried out by synthesized α-pinene into borneol through sodium reduction using twoalkali e.i KOH and NaOH. The compounds were characterized by FTIR, NMR and GCMS. The results showed that onFTIR analysis of 12 samples of the borneol synthesized showed fairly similar absorption peaks with peaks appearing on standardborneol FTIRs. The NMR analysis of both HNMR and CNMR, compared with the standard NMR compounds α-pinene,champor and borneol, show that the peaks still show differences. The GCMS result showed the formation of the compound ofborneol compound with the percentage of 0.12 to 2.2% relatives. The type of base and origin of the turpentine used did not showany difference in borneol yield.